Misfortune Prediction of Restricted Marriage of Lep Tarjha in Tlagah Village of Banyuates Sub-District - Laily Nur Arifa; Abdul Azis (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
Lep Tarjha according to the concept of TlagahBanyuatesSampang society refers to marriage between two families that share the same lineage with another couple in the efamilies. Unfortunately, Madurese people believe that this practice will create misfortunate events for the families. The misfortune can be in the form of math (death), ke’ sakean (susceptible to diseases), difficulty earning income, frequent problems, and/ or unhappiness. People strongly believe the LepTarjhâ marriage can create impacts in the form of misfortunes. Therefore, whenever there is LepTarjhâ marriage practice, the society will consider the couple as inviting the misfortunes and disasters. The misfortunes pattern due to the LepTarjhâ marriage practice is varied, such as income-earning difficulty, problem-prone situation, unhappy marriage, susceptibility to diseases, unpleasant response and treatment from families and neighbors, death, and divorce. Based on the point of view of sad al-dzari'ah, the LepTarjhe is concluded as a disputed practice in terms of its legal basis. The practice then resulted in the division of society into two: people who believe in the impact of the LepTarjhe tend to forbid the practice, and those who do not believe in it allow the practice to continue